Angels & demons - Brown, Dan, 1964- (Emily Bestler Books/Atria, 2021)
World-renowned Harvard symbologist Robert Langdon is summoned to a Swiss research facility to analyze a cryptic symbol seared into the chest of a murdered physicist. What he discovers is unimaginable: a deadly vendetta against the Catholic Church by a centuries-old under-ground organization -- the Illuminati. In a desperate race to save the Vatican from a powerful time bomb, Langdon Joins forces in Rome with the beautiful and mysterious scientist Vittoria Vetra. Together they embark on a frantic hunt through sealed crypts, dangerous catacombs, and deserted cathedrals, and into the depths of the most secretive vault on earth...the long-forgotten Illuminati lair.